Implementasi Pendekatan Science, Technology, Engineering, and Mathematics untuk Meningkatkan Kemampuan Literasi Sains dan Kreativitas Siswa - Widya Astuti*; Sulastri Sulastri; Muhammad Syukri; Abdul Halim (Jurnal Pendidikan Sains Indonesia, 2023)
Current learning problems affect the low scientific literacy and creativity of students, so an approach is needed that is able to link science, technology, and society. The era of 21st century education and the development of the 2013 curriculum requires students to be creative and independent, so that they can improve better learning outcomes. This study aims to determine the differences in students' scientific literacy and creativity through the implementation of the STEM approach at SMP Negeri 2 Sigli. The research method used was pre- experimental with one group pretest posttest design. The research instrument consisted of scientific literacy questions, student creativity observation sheets and interview sheets. The results showed that the implementation of the STEM approach could improve students' scientific literacy with an average N-gain 0.74 in the high category. The average difference test results obtained a significance value of 0.000 0.05, meaning that there are differences in scientific literacy after the implementation of the STEM approach. This proves that the STEM approach can improve students' scientific literacy and student creativity as measured by three indicators. The three indicators measured are generating, planning and, producing, so that the scores obtained from the three indicators are included in the high category. The conclusion in this study is that students' scientific literacy and creativity increase through the STEM approach